The potential roles of herpesvirus and cytomegalovirus in the exacerbation of pemphigus vulgaris - Mohammadi, Fariba; Khalili, Zahra; Marashi, Sayed Mahdi; Ehsani, Amirhoushang; Daneshpazhooh, Maryam; Teymoori-Rad, Majid; Balighi, Kamran; Nejati, Ahmad; Shahmahmoodi, Shohreh; Izadidakhrabadi, Shima; Mahmoudi, Hamidreza; Noormohammadpour, Pedram (Dermatology practical & conceptual, 2018)
Background: Among exogenous etiologies, the critical role of microbial agents such as herpesviruses (HSV1/2) and cytomegalovirus (CMV) in triggering and flaring autoimmune conditions such as pemphigus vulgaris (PV) has been recently discovered. Objectives: The present study aimed to investigate the plausible role of these viruses in the exacerbation of PV using serological and molecular methods. Patients/Methods: Sixty patients with PV (30 with relapse type and 30 with remission type) were recruited for the purpose of this case-control study. Skin, mucosal, and throat specimens were obtained and examined for viruses by reverse transcriptase polymerase chain reaction. To determine the immunoglobulin G (IgG) titer, enzyme-linked immunosorbent assay was used. Results: Desmoglein1-specific IgG was positive in 56.7% of patients with the relapse form and in 20.0% of those with the remission form indicating a significant difference across the 2 groups (P = 0.003), but the rate of positivity for desmoglein3-specific IgG in the relapse and remission types was 76.7% and 63.3%, respectively, with no significant difference (P = 0.260). There was no difference in the mean levels of HSV-IgG and CMV-IgG in the relapse and remission groups. HSV and CMV positivity in PV patients was independent of the site of the samples. Using the multivariable linear regression model, the level of CMV-IgG in PV patients was directly affected by female sex and advanced ages. Conclusions: Our study could not demonstrate the role of HSV1/2 and CMV as triggering factors for PV exacerbation. Further studies are needed to evaluate the potential role of these viruses in PV exacerbation especially considering demographic variables.